Perlindungan Hukum Bagi Istri Sebagai Korban Kekerasan Dalam Rumah Tangga (KDRT) Menurut Undang-Undang Nomor 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga - al Asyari, Muhammad Arif; F. Yulianis, M. Sifa’ (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study is to discuss and analyze legal protection for wives of victims of domestic violence (KDRT) according to Law Number 23 of 2004 concerning the Elimination of Domestic Violence and discuss and analyze the constraints in legal protection for wives of victims of domestic violence (KDRT). This research is included in juridical research. The results showed that legal protection for wives as victims of domestic violence according to Law Number 23 of 2004 concerning the Elimination of Domestic Violence can be carried out preventively and repressively. Legal protection for wives as victims of domestic violence is preventively carried out by strengthening social networks, understanding local cultural wisdom and practicing religious teachings, as well as strengthening the foundation and economic building of the family. Meanwhile, legal protection for wives as victims of domestic violence is repressively carried out with temporary protection and protection based on court determinations. The results also showed that obstacles in legal protection for wives of victims of domestic violence include: these law enforcement officials have not been able to provide optimal protection and assistance for victims in implementing the Law on the Elimination of Domestic Violence, safe and legal assistance is still scarce and most are still difficult to access victims and the handling units for women and children who are victims of violence are not equipped with Adequate infrastructure.